Myeloid depression follows infection of susceptible newborn mice with the parvovirus minute virus of mice (strain i). - Segovia, J C (1995)
The in vivo myelosuppressive capacity of strain i of the parovirus minute virus of mice (MVMi) was investigated in newborn BALB/c mice inoculated with a lethal intranasal dose. MVMi infection reached maximum levels of DNA synthesis and infectious titers in lymphohemopoietic organs at 4 to 6 days postinoculation and was restricted by an early neutralizing humoral immune response. After viral control (by 10 days postinoculation), a significant decrease in femoral and splenic cellularity, as well as in granulocyte-macrophage colony-forming unit and erythroid burst-forming unit hemopoietic progenitors, was observed in most inoculated animals. This delayed myeloid depression, although it may be not a major cause of the lethality of the infection, implies indirect pathogenic mechanisms induced by MVMi infection in a susceptible host.